2013 13th IEEE International Conference on Nanotechnology (IEEE-NANO 2013) 2013
DOI: 10.1109/nano.2013.6720994
|View full text |Cite
|
Sign up to set email alerts
|

Statistical device simulation of intrinsic parameter fluctuation in 16-nm-gate n- and p-type Bulk FinFETs

Abstract: In this paper, we estimate the influence of random dopants (RDs), interface traps (ITs), and random work functions (WKs) using the experimentally calibrated 3D device simulation on DC characteristic of high-κ / metal gate n-and p-type bulk fin-typed field-effect-transistors. We further study these intrinsic parameter fluctuations' impact on drain induced barrier lowering (DIBL). The main findings of this work show the RDF and WKF on n-type device are larger than that of p-type one. The DIBL is dominated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Recent studies reported the density of interface traps ( D it ) resulting from the orientations of the vertical fin channel of FinFETs [ 6 , 17 ]. The effects of RITs on sub-22-nm FinFETs have also been reported and compared between different device structures [ 18 , 19 ]. Unfortunately, the impact of RITs on 16-nm-gate HKMG bulk FinFET devices has not been clearly discussed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported the density of interface traps ( D it ) resulting from the orientations of the vertical fin channel of FinFETs [ 6 , 17 ]. The effects of RITs on sub-22-nm FinFETs have also been reported and compared between different device structures [ 18 , 19 ]. Unfortunately, the impact of RITs on 16-nm-gate HKMG bulk FinFET devices has not been clearly discussed yet.…”
Section: Introductionmentioning
confidence: 99%